Perbandingan keputusan multi-atribut berasaskan beberapa teori set - Zamali Tarmudi,; Abu Osman Md Tap,; Mohd Lazim Abdullah, (Penerbit ukm, 2009)

(untitled)
This paper discusses the comparison analyses for multi-attributes decision derived from crisp set, fuzzy set, intuitionistic fuzzy set and conflicting bifuzzy set. It focuses on the different evaluation approach using the binary system in crisp sets, the membership degree in [0,1] for fuzzy sets, the membership and non-membership degrees with condition 0 ≤ μA(x) + γA(x) ≤ 1 in intuitionistic fuzzy sets, and ‘equilibrium evaluation approach’ (i.e., positive and negative aspects) in conflicting bifuzzy sets. To meet these objectives, all the set theories are briefly discussed specifically the definitions, equalities, the differences as well as the different evaluation approaches to obtain the relative approximation index. A numerical example using Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is also presented to clarify each of the above set theories. From the calculation results, it shows the significant differences of relative approximation index for each theory and different rating between the crisp set and other set theories. It is also found that all the set theories have recorded the same rating and consistent, except crisp sets. Thus, this situation offers wider opportunities to investigate more deeply and holistically for future research